EMOSI TOKOH MORIGUCHI YUKO DALAM NOVEL CONFESSIONS KARYA MINATO KANAE (KAJIAN PSIKOLOGI SASTRA) - Amanda Oktafiani; Sainil Amral; Supriyati Supriyati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the emotions of the character Moriguchi Yuko in Minato Kanae's novel Confessions. The analysis of this study will answer the research questions and objectives, which are to describe the emotions of joy, anger, sadness, fear, hatred, surprise, and love. This research will illustrate how emotional expressions function to create a realistic impression that can be felt by the audience in literary works, especially novels. The research method used to collect and analyze the research data is a qualitative descriptive method, which allows the researcher to describe the emotional expressions of the seven emotions studied. With this research method, the researcher can describe the research results on how the forms of emotions convey happy emotions, angry emotions, sad emotions, fearful emotions, hateful emotions, surprised emotions, and loving emotions in the novel. The research results indicate that the form of emotion of the character Moriguchi Yuko in the novel Confessions by Minato Kanae tends toward the form of emotion that conveys a real impression in the novel. This is evident in the quotations found in the form of happy emotions 14 quotations, angry emotions 24 quotations, sad emotions 22 quotations, fearful emotions 14 quotations, hateful emotions 23 quotations, surprised emotions 29 quotations, and loving emotions 21 quotations. In other words, the total number of emotional expressions found in this novel is 147 quotes.